THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK ENGAGEMENT, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PUBLIC WORKS AND SPATIAL PLANNING OFFICE, NORTH SUMATRA - Lutvi Noviyanti; Anggia Sari Lubis; Rukmini; Toni Hidayat (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to describe the influence of transformational leadership, work engagement, and organizational culture on the performance of employees of the Public Works and Spatial Planning Office of North Sumatra Province. The data analysis method uses a descriptive data analysis method with a quantitative approach. The population and sample in this study were 62 employees which were determined based on the saturated sampling technique method. The data collection techniques in this study are observation, documentation, and questionnaires with a Likert Scale data measurement scale. The data analysis technique used validity, relibiality, classical classical assumption test, multiple linear regression analysis, and hypothesis test. Data processing uses SPSS Version 20.0. The results of the study prove that transformational leadership, work engagement and organizational culture have a positive and significant effect on employee performance. Simultaneously, the results of transformational leadership, work engagement and organizational culture have a positive and significant effect on the performance of employees at the Public Works and Spatial Planning Office of North Sumatra Province. With a value of Fcount (79.497) > Ftable (2.76) and a significance value of 0.000 < 0.05.